Volumetric Reductions of Subcortical Structures and Their Localizations in Alcohol-Dependent Patients - Shim, Jae-Hyuk; Kim, Yong-Tae; Kim, Siekyeong; Baek, Hyeon-Man (Frontiers in Neurology, 2019)
Background Changes in brain morphometry have been extensively reported in various studies examining the effects of chronic alcohol use in alcohol dependent patients. Such studies were able to confirm the association between chronic alcohol use and volumetric reductions in subcortical structures using FSL (FMRIB software library). However, each study that utilized FSL had different sets of subcortical structures that showed significant volumetric reduction. First, we aimed to investigate the reproducibility of using FSL to assess volumetric differences of subcortical structures between alcohol dependent patients and control subjects. Second, we aimed to use Vertex analysis, a less utilized program, to visually inspect 3D meshes of subcortical structures and observe the localized areas where volumetric reduction occurred on each subcortical structure. Methods We analyzed the volumes of 14 subcortical structures (bilateral thalamus, caudate, putamen, globus pallidus, hippocampus, amygdala, nucleus accumbens) in 21 alcohol dependents and 21 healthy controls using images acquired with 3T MRI. The images were run through various programs found in FSL, such as SIENAX, FIRST, and Vertex analysis. Results We found that in alcohol dependent patients, bilateral thalamus (left: p < 0.01, right: p = 0.01), bilateral putamen (left: p = 0.02, right: p < 0.01), right globus pallidus (p < 0.01), bilateral hippocampus (left: p = 0.05, right: p = 0.03) and bilateral nucleus accumbens (left: p = 0.05, right: p = 0.03) were significantly reduced compared to the corresponding subcortical structures of healthy controls. With vertex analysis, we observed surface reductions of the following hippocampal subfields: Presubiculum, hippocampal tail, hippocampal molecular layer, hippocampal fissure, fimbria, and CA3. Conclusions We reproduced the assessment made in previous studies that reductions in subcortical volume was negatively associated with alcohol dependence by using FMRIB Software Library. In addition, we identified the subfields of the thalamus and hippocampus that showed volumetric reduction.